Practical Python Data Visualization : A fast track approach to learning data visualization with Python - Pajankar, Ashwin (USA : Apress, 2021)
You will be empowered by the knowledge of data visualization with Python and will be able to apply this knowledge in real-life projects at your workplace. It will also instill confidence in you to explore more libraries for data visualization in Python, as most of the support the scientific Python ecosystem and NumPy library discussed in detail in this book.
Keywords: Data Visualization; Python